Meta-analysis and review of dopamine agonists in acute episodes of mood disorder: Efficacy and safety. (April 2018) - Romeo, Bruno; Blecha, Lisa; Locatelli, Katia; Benyamina, Amine; Martelli, Catherine
The objective of this meta-analysis is to assess the efficacy and safety of partial and complete dopamine agonists in the treatment of acute mood disorder episodes. Randomized, double-blind and placebo-controlled trials of dopamine agonists in the treatment of acute mood disorder episodes were identified in the MEDLINE and PsycINFO databases and included in the meta-analysis. In monotherapy of mania, improved remission rates were found for cariprazine (odds ratio (OR): 2.08, P < 0.01) and for high-dose aripiprazole (OR: 3.00; P = 0.05), but not for low-dose aripiprazole. In bipolar depression, no improvement of remission and response rates was found for aripiprazole in monotherapy, whereas improved response rate (OR: 10.27, P < 0.01) was found for pramipexole only as an add-on to another mood stabilizer. In major depressive disorder, relatively similar improvements of remission rates were found for high-dose (OR: 1.96, p < 0.01) and low-dose aripiprazole (OR: 1.68, P = 0.01), as well as brexpiprazole (OR: 1.52, P = 0.05) as an add-on to antidepressant medication. Our meta-analysis shows that partial dopamine agonists at high doses are effective in treating acute mania. In major depressive disorder, which is resistant to classical antidepressants, low doses of partial dopamine agonists as adjunct therapy may represent a relatively safe and effective alternative.